2023
DOI: 10.1108/jwl-12-2022-0168
|View full text |Cite
|
Sign up to set email alerts
|

Making evidence-based practice actionable in the social service context: experiences and implications of workplace education

Birgitta Schwartz,
Karina Tilling

Abstract: Purpose Research and experience show that evidence-based practice (EBP), i.e. using the best available knowledge in daily professional work, is difficult to achieve in social services. The purpose of this study is to understand the development of organizational EBP learning processes in daily work through workplace education for staff and managers of supported homes for people with cognitive disabilities. The authors examine how the EBP model and new knowledge are understood and made actionable in the workplac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Evidence-based medicine has been developing since the 1990s to offer a new methodology and approach to evidence transferred and incorporated in other sciences (Schwarz & Tilling, 2023;Reiss, 2016;Mahmoudi et al, 2024;. The first publications on specific issues of evidence-based social sciences and practices first appeared on the turn of the century (Ackers, 2000;Humphries, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence-based medicine has been developing since the 1990s to offer a new methodology and approach to evidence transferred and incorporated in other sciences (Schwarz & Tilling, 2023;Reiss, 2016;Mahmoudi et al, 2024;. The first publications on specific issues of evidence-based social sciences and practices first appeared on the turn of the century (Ackers, 2000;Humphries, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Practices and hierarchy of evidence across disciplines and sectors are subject to great variance. All sectors and disciplines seem to be studied individually (Harris & Williams, 2019;den Heyer, 2022;Schwarz & Tilling, 2023). The pilot searches of the Scopus database, Semantic scholar, and Research Gate have found neither reviews of evidence-based sciences, nor research on the evidence-based methodology in social sciences across disciplines.…”
Section: Introductionmentioning
confidence: 99%